Analysis of Disruption of Consumer Buying Interest in Cake Products at Mom's Shop During the Pandemic - Hesti Ningrum Naufal Urbach (INCOME: Innovation of Economics and Management, 2023)
This study aims to find out what can affect the decline in consumer buying interest in pastry products at MSME Mom's Shop during the pandemic. The type of research used in this research is descriptive qualitative. In this study, researchers conducted interviews with consumers of the MSME Mom's Shop business as well as the owners and processors of the business. Researchers analyzed some that have been found, how are the factors that can affect consumer buying interest. In this study, researchers found four factors that influence consumer buying interest in pastries. Four factors were found, namely, the factor of making their own, being skilled at other stores, economic factors, and switching to online stores rather than the MSME Mom's Shop business which had to leave the house.